Outperformed: Exploration and Comparison of the Tongue-And-Cheek Tragedies of Women-Animal Relationships in Selected Short Stories by Samanta Schweblin and in Apichatpong Weerasethakul’s Film, Uncle Boonmee Who Can Recall His Past Lives - Sawnie Smith (Vernacular: New Connections in Language, Literature, & Culture, 2020)
The unsettling short stories that comprise Samanta Schweblin’s 2008 collection Pájaros en la boca are textured and populated by the flesh of not only humans, but also the skins of species that belong to a wider zoological and mythical scope. Those creatures in Schweblin’s literary output who possess scales, feathers, and wings find themselves variously rubbing up against, crushed under, and orally engulfed by human dermis. This essay seeks to explore the charge of gender politics that courses through interactions between human women and (demi-) animals in two short stories from this collection: “El hombre sirena” and “Olingiris”—animal contact with female, human dermis. But first, a filmic parallel for such interactions is introduced: a scene from Thai director Apichatpong Weerasethakul’s award-winning 2010 film, Uncle Boonmee Who Can Recall His Past Lives in which a catfish sexually gratifies a princess. This essay argues that both Schweblin’s short fictions—in which the close ties that are stitched together between women and animal are often saturated with a certain eroticism—and Weerasethakul’s princess-catfish scene telegraph the same message: the potential for sexual pleasure and release among human women—locked into oppressive, patriarchal worlds—seems available only through exchanges with the animate but nonhuman. Interestingly and ironically, these (demi-) animals in both film and literature are marked as male. As such, this essay argues that both of Schweblin’s relevant short stories as well as Weerasethakul’s princess-catfish scene succeed in reorienting, poking fun at, and sharply criticizing the immense corpus of principally Western imagery of woman-animal sexual encounters that situates women and girls within imagined (and sometimes historicized) landscapes where they are deemed ripe subjects for rape—women and girls who are forcibly overwhelmed by and within the sexual performances of animals and flattened into narrative tools for misogynistic didactics.
Keywords: Samanta Schweblin; Bestial Rape; Women; Animal; Aping